Analisis Program Bina Diri Sebagai Upaya Kemandirian Anak Tuna Daksa Di Yayasan Pembinaan Anak Cacat Kota Medan - Aidil Aldan (Universitas Muhammadiyah Sumatera Utara, 2022)
Physical disability is a condition that is damaged or disturbed as a result of impaired shape or resistance to bones, muscles, and joints in their normal function. This condition can be caused by illness, accident or can also be caused by congenital. Therefore, children with disabilities must receive special education through special schools where there is a Self Development Program for the independence of children with disabilities, especially at Yayasan Pembinaan Anak Cacat Kota Medan. The research was conducted at Yayasan Pembinaan Anak cacat Medan with Disabilities in Medan. The key informants in this study were the Principal of the SLB-D School and the teachers at Yayasan Pembinaan Anak Cacat Kota Medan. Data collection techniques with literature study, observation, and interviews. The data obtained in the field were then analyzed by researchers who described it with a qualitative approach. Finally, conclusions can be drawn from the results of this study. The results showed that the Self Development Program was carried out through an assessment carried out by teachers on children with disabilities to determine the needs and abilities of each child with disabilities in their respective classes. The Self Development Program analysis uses general ADL activities (Activities of Daily Living General Classification), namely self-care activities, ambulation or movement activities and hand activities.